2021
DOI: 10.12681/jhvms.26760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Milk Yield and Milk Composition of Honamlı Goats

Abstract: The aim of this study was to determine the milk yield and milk composition (total solids, fat, protein and lactose), freezing point depressionand somatic cell counts of Honamlı goat during second lactationin Turkey. The animal material of the study consisted of a total of 30 goat. Total milk yield was detected by using Fleischmann’s method. Milk composition was analyzed by Bentley 150, and somatic cells were counted by Bentley Somacount FC. One-way ANOVA was used to determine the effect of lactation stages on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…This result is higher than that reported by Al-Azzawi ( 2017 In the same context, the overall mean of the LP was estimated as 199±1.23 days (Table 2). This estimate is lower than that demonstrated by Yakanet The overall mean of DMY was estimated as 2.1±0.02 kg (Table 2), which is greater than estimates of 0.99 kg, 0.7 kg, 1.4 kg, and 0.45 kg reported by Bermejo et al (2020), Marković et al (2020), Suranindyah et al (2020), andAkbaş et al (2021) in Murciano-Granadina goats in Spain, local Balkan goats in India, Etawah crossed goats in Indonesia, and Honamlı goats in Turkey, respectively. However, the current estimate is lower than that found by Kunbharet al (2016) of 2.7 kg in Kamori goats in Pakistan.…”
Section: Type Of Birthcontrasting
confidence: 55%
“…This result is higher than that reported by Al-Azzawi ( 2017 In the same context, the overall mean of the LP was estimated as 199±1.23 days (Table 2). This estimate is lower than that demonstrated by Yakanet The overall mean of DMY was estimated as 2.1±0.02 kg (Table 2), which is greater than estimates of 0.99 kg, 0.7 kg, 1.4 kg, and 0.45 kg reported by Bermejo et al (2020), Marković et al (2020), Suranindyah et al (2020), andAkbaş et al (2021) in Murciano-Granadina goats in Spain, local Balkan goats in India, Etawah crossed goats in Indonesia, and Honamlı goats in Turkey, respectively. However, the current estimate is lower than that found by Kunbharet al (2016) of 2.7 kg in Kamori goats in Pakistan.…”
Section: Type Of Birthcontrasting
confidence: 55%
“…In a previous study conducted on the same area, the major fatty acids (FAs) in ovine milk were found to be palmitic and oleic acids [ 69 ]. The importance of lipids in sheep milk lies not only in their high nutritional value but also to their effect in the taste and flavour as well as in the manufacturing properties of the dairy products [ 70 , 71 ]. In comparison to the other ruminants’ milk, sheep milk has higher total fat and conjugated linoleic acid (CLA) content [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%